The Expression Of Cd4+ Lymphocytes Of Bali Cattle After Consuming Mixed Mirerals - Suwiti, Ni Ketut; Windhu, M; Watiniasih, Ni Luh; Besung, I Nengah Kerta; Suartha, I Nyoman (Advances in Tropical Biodiversity and Environmental Sciences, 2018)
Minerals play an important role in activating the lymphoid cells. Mineral deficiency can cause interference prolifrasi in lymphocytes, particularly the expresion of CD4 +. Bali cattle are hardly given additional mineral due to cattles are in semi-intensive breeding method. Therefore, this study aims to determine the expression of CD4 + lymphocytes Bali cattle after consuming of mixed mineral. The samples used were 32 male bali cattles reared in the village of Catur, Kintamani, Bangli regency. Samples were divided into 2 groups, those were: 16 individul of bali cattle was given 7.5gr additional of  mixed mineral per individual / day, and theother 16 individual as acontrol. The treatmnes were conducted for 3 months. The results showed that administration of 7.5gr mixed mineral per individual/day did not show differences in the expression of CD4 + lymphocyte of bali cattle.